Defining Design and Technology in an Age of Uncertainty: The View of the Expert Practitioner - Wooff, David (PRISM: Casting New Light on Learning, Theory and Practice, 2018)
Long standing debate surrounds the position that Design and Technology holds in the English and Welsh national curriculum. Some commentators espouse alignment with Science, Technology, Engineering and Mathematics (STEM) as its natural home, whilst others argue that this stifles creativity and takes no account of the ‘designerly’ nature they consider to be a central tenet of the subject. Against this backdrop, the subject has undergone changes in both prescribed subject knowledge content and examination and assessment arrangements by which pupil progress and attainment are measured. Set against this background, the work presented here summarises a Delphi study which sought to canvass established and experienced Design and Technology teachers about how they perceive the attributes, values and unique features of the subject. The results are analysed to give a view of the subject from within the classroom. Analysis reveals that participants in the study consider the ‘uniqueness’ of the subject to prevail over the values and attributes they collectively define it by. The study moves on to discuss the findings in relation to the values and direction which underpin the policy documentation that drives and shapes the subject from a national perspective. Finally, the work concludes by highlighting several important areas worthy of further research which have emerged and could be seen as contributory to understanding the nature and essence of Design and Technology.